EFEKTIVITAS PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP PENINGKATAN KESEJAHTERAAN PETANI DI DESA SALO DUA KECAMATAN MAIWA KABUPATEN ENREKANG - Syarifuddin, Renny; Adnan, Andi Astina; Uceng, A (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the Effectiveness of Village-Owned Enterprise Management (BUMDes) towards Improving the Welfare of Farmers. The population in this study was 35 members of Village-Owned Enterprises (BUMDes) from January to March in Salo Dua Village, Maiwa District, Enrekang Regency. The sampling technique uses a saturated sample where the entire population is sampled. This type of research is quantitative descriptive. The data collection techniques used in this research are, observation, literature study and questionnaire. The data analysis technique used is a validity test, reliability, using the help of the IBM SPSS statistic 26.0 Application. The results of this study found that the Effectiveness of Village Owned Enterprise Management (BUMDes) from the results of the questionnaire was obtained by a variable recapitulation. The effectiveness of 60% is in the